High-response electrorheological servo valve. (January 2020) - Heinken, Helge; Ulrich, Stephan; Bruns, Rainer; Schneider, Steffen
The demand of more powerful and high-dynamic hydraulic actuators gives the servo valve as a control member an increasingly important role. The valve should provide the hydraulic actuator with sufficient volume flow over wide frequency range to achieve large strains at high operating frequencies. Here, the electrorheological effect as an electrohydraulic valve drive offers great potential. It converts the electrical input signal directly into a controlling mechanical quantity within a few milliseconds and provides theoretically unlimited strain. Thus, the electrorheological effect has the ability to increase the performance of conventional hydraulic systems. This work presents a two-stage servo valve with an electrorheological pilot stage. Furthermore, it introduces a model to describe the static and dynamic properties of the system. The model is validated on the basis of measurement results.